CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
Aims Vascular calcification is a common clinical complication of chronic kidney disease (CKD), atherosclerosis (AS), and diabetes, which is associated with increased cardiovascular morbidity and mortality in patients. The transdifferentiation of vascular smooth muscle cells (VSMCs) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but whether it regulates the calcification of arteries and VSMCs remains unclear. Therefore, this study aims to understand the role of C/EBPα in the regulation of vascular calcification. Methods and Results Both mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). Upregulation of C/EBPα was also observed in the high phosphate- and calcium-induced VSMC calcification process. The siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, C/EBPα depletion in VSMCs significantly reduced the mRNA expression of the osteochondrogenic genes, e.g., sex-determining region Y-box 9 (Sox9). C/EBPα overexpression can induce SOX9 overexpression. Similar changes in the protein expression of SOX9 were also observed in VSMCs after C/EBPα depletion or overexpression. In addition, silencing of Sox9 expression significantly inhibited the phosphate- and calcium-induced VSMC calcification in vitro. Conclusion Findings in this study indicate that C/EBPα is a key regulator of the osteochondrogenic transdifferentiation of VSMCs and vascular calcification, which may represent a novel therapeutic target for vascular calcification.